To What Extent Do Brand Image and Perceived Value Contribute to Customer Trust and Purchase Decisions for Local Skincare Products in Indonesia? - Dila Padila Nurhasanah; Dasa Rahardjo Soesanto; Ilham Akbar Bunyamin (West Science Journal Economic and Entrepreneurship, 2026)
The rapid growth of the local skincare industry in Indonesia has intensified competition among domestic and international brands, making it essential to understand the factors that influence consumer purchasing behavior. This study aims to examine the extent to which brand image and perceived value contribute to customer trust and purchasing decisions regarding local skincare products in Indonesia. A quantitative research approach was employed using a survey method. Data were collected from 250 consumers who had purchased and used local skincare products through a structured questionnaire measured on a five-point Likert scale. The collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The findings reveal that brand image and perceived value significantly and positively influence customer trust. Brand image and perceived value were found to enhance consumers’ confidence in local skincare brands. Furthermore, brand image, perceived value, and customer trust significantly influence purchasing decisions. The results also demonstrate that customer trust partially mediates the relationships between brand image and purchasing decisions, as well as between perceived value and purchasing decisions. The structural model explains 61.8% of the variance in customer trust and 72.1% of the variance in purchasing decisions, indicating substantial explanatory power. The study concludes that customer trust plays a crucial role in translating favorable brand perceptions and value evaluations into actual purchasing decisions. These findings contribute to consumer behavior and marketing literature by providing empirical evidence from the Indonesian local skincare market. Practically, the results suggest that local skincare companies should focus on strengthening brand image, delivering superior perceived value, and fostering customer trust to enhance consumer purchasing decisions and maintain competitive advantage in the increasingly dynamic beauty industry.